Contrasting effects of space and environment on functional and phylogenetic dissimilarity in a tropical forest. (20th July 2018) - Asefa, Mengesha; Brown, Calum; Cao, Min; Zhang, Guocheng; Ci, Xiuqin; Sha, Liqing; Li, Jie; Lin, Luxiang; Yang, Jie
Abstract: Aims: The evolutionary history and functional traits of species can illuminate ecological processes supporting coexistence in diverse forest communities. However, little has been done in decoupling the relative importance of these mechanisms on the turnover of phylogenetic and functional characteristics across life stages and spatial scales. Therefore, this study aims to estimate the contribution of environment and dispersal on the turnover of phylogenetic and functional diversity across life stages and spatial scales, in order to build a coherent picture of the processes responsible for species coexistence. Methods: We conducted the study in Xishuangbanna Forest Dynamics Plot in Yunnan Province, southwest China. We used four different spatial point process models to estimate the relative importance of dispersal limitation and environmental filtering. The functional traits and phylogenetic relationships of all individual trees were incorporated in the analyses to generate measures of dissimilarity in terms of pairwise and nearest-neighbor phylogenetic and functional characteristics across life stages and spatial scales. Important Findings: We found non-random patterns of phylogenetic and functional turnover across life stages and spatial scales. Environmental filtering structured pairwise phylogenetic and functional beta diversity across spatial scales, while dispersal limitation alone, and in combination with environment filtering, shaped nearest neighbor phylogenetic and functional beta diversity. The relative importance of dispersal limitation and environmental filtering appeared to change with life stage but not with spatial scale. Our findings suggest that phylogenetic and functional beta diversity help to reveal the ecological processes responsible for evolutionary and functional assembly and highlight the importance of using a range of different metrics to gain full insights into these processes.